Management of Life Skills Education in Tsanawiyah Madrasah, Muara Bangkahulu District - Hamdani Hamdani; Idi Warsah; Alfauzan Amin; Adisel Adisel (Budapest International Research and Critics University, 2022)
This research is motivated by the problem of the gap between the theory and concept of education management and the practice of management of life skills education at Madrasah Tsanawiyah Islamic Boarding School in Muara Bangkahulu District. So even though life skills education has been held at the madrasa, its management is not running optimally. Therefore, the author is interested in raising the issue of life skills education management in Madrasah Tsanawiyah. This research is a qualitative research conducted with a non-participant observation approach (observation is not involved). Data were collected by three methods: documentation, interviews and observation. The analysis used in this research is descriptive analysis (description), because the data collected to examine the data is qualitative. The results of this study include three things. First, the management of life skills education at Madrasah Tsanawiyah Islamic Boarding School in Muara Bangkahulu District did not run optimally, because it did not go through the four stages of management properly, namely: planning, organizing, directing and supervising. Second, the factors that influence the non-optimal management of life skills education consist of two parts. (1) Internal factors, in the form of (a) educational orientation which emphasizes the religious aspect so that human resources for skilled teachers receive less attention; (b) lack of allocation of funds for the development of life skills education; and (c) lack of understanding of modern management by the management of the Islamic boarding school. (2) External factors consist of: (a) lack of government assistance; and (b) people's perception that they do not see the importance of life skills education in Islamic boarding schools. Third, the efforts that have been made to improve life skills education are still limited to the procurement of computer and sewing skills teachers; involve students in planting activities on the plantations of Islamic boarding schools, and schedule skills activities.